COMMUNICATION STEREOTYPES OF FEMALE SMOKERS: A Case Study on Teenage Employees at Point Pool & Lounge in Kupang City - Mandolang, Wesley; Andung, Petrus Ana; Sowe Leuape, Emanuel (ASPIRATION Journal, 2022)
There are many female smokers in Kupang City and they are often encountered. One of them is at the entertainment venue, Point Pool & Lounge. This has made the researcher interested in studying further the communication of stereotypes towards female smokers. The purpose of this study is: to describe the communication of stereotypes towards teenage female smokers who work at Point Pool & Lounge and 2 to find out the reasons women become smokers who work at Point Pool & Lounge. This type of research is qualitative with a case study method. The theory used is Labeling Theory. Data collection techniques in this study are in-depth interviews, documentation, and observation. The results of this study show that (1) female smokers are seen as naughty women and they get a double stigma in their interaction with the social environment and (2) the reason teenage girls smoke is due to social factors and cigarettes as a medium of expression as well as changes in social construction and lifestyle.